POEM "RUANG HIJAU" BY NATASHA RIZKY AND EMOTIONAL EXPRESSION: THE PSYCHOLOGY OF LITERATURE STUDY - Azhari; Yeni Artanti; Muhammad Zikrullah; Dinda Destari (Literature and Literacy, 2024)
Poetry is one of the literary works whose emotional expression is sometimes difficult to understand. The purpose of this study is to investigate the expression of emotion and its meaning in the poem "Ruang Hijau" by Natasha Rizky. This research implements a descriptive-qualitative paradigm type. Data was obtained from a book entitled "Kamu Tidak Istimewa." This book was written by Natasha Rizky herself. Published by Elex Media Komputindo. The data was obtained by copying and documenting it in a research draft. The process of data analysis in this study involves analysis involving data texts and in-depth analysis of each data text, followed by status analysis. The data text of the book was carefully read line by line to find the essence of each narrative by numbering each line. The results show that this poem contains only two emotional expressions, namely the emotional expressions of sadness and fear. While the expressions of joy, courage, and anger are not found in the poem, Expressions of sadness mean that sadness, pain, and fatigue are experienced. Expressions of fear mean weakness in the face of pressure, while the narrative of struggle symbolizes her hope for help. It also has the meaning of loneliness and longing for help from others.